Resolution of polyphyly in Pueraria (Leguminosae, Papilionoideae): The creation of two new genera, Haymondia and Toxicopueraria, the resurrection of Neustanthus, and a new combination in Teyleria - Egan, Ashley N.; Pan, Bo (Phytotaxa, 2015)
Recent molecular phylogenetic studies (Egan et al., in prep.) have demonstrated widespread polyphyly within the genus Pueraria. A new classification is presented here that delineates monophyletic groups previously considered congeneric with Pueraria. This taxonomic treatment provides several new species combinations and a more natural circumscription of Pueraria by reinstating the genus Neustanthus, transferring one species to Teyleria and establishing two new genera: Haymondia and Toxicopueraria.